Teaching Computing on Basic Education with Robotics - Cunha, Felipe; Nascimento, Cristiane (Anais do Simpósio Brasileiro de Robótica e Simpósio Latino Americano de Robótica (SBR/LARS), 2019)
This paper shows an approach to teaching the fundamentals of computer science on basic education through educational robotics. The approach was evaluated with students from the 3rd, 4th and 5th grades of elementary school. Results show better performance among participants who received stimuli from robotics.